2017
DOI: 10.5334/hpb.3
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Intervention Preferences and Physical Activity Motivation of People with Depressive Symptoms

Abstract: Physical activity is an effective method for managing depressive symptoms, and web-based interventions may be an effective tool for promoting physical activity within this population. People with depressive symptoms may experience condition-specific facilitators and barriers to be considered when developing physical activity interventions. This study provides insight into web-based physical activity intervention preferences and physical activity motivation of people with depressive symptoms. This study was par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
(31 reference statements)
1
3
0
Order By: Relevance
“…The current study demonstrated that the psychiatric symptoms such as hallucinations and paranoid delusions seen in the majority of the patients prevented them to attend physical activities. Similar findings were reported in other studies in the literature . A qualitative study by Johnstone et al .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The current study demonstrated that the psychiatric symptoms such as hallucinations and paranoid delusions seen in the majority of the patients prevented them to attend physical activities. Similar findings were reported in other studies in the literature . A qualitative study by Johnstone et al .…”
Section: Discussionsupporting
confidence: 91%
“…In addition, they reported that the company of the individuals with similar mental health issues facilitated their attendance to the physical activities . The study by Alley et al . reported that the individuals with mental illness’ will for healthy lifestyles and for the control of body weight was motivating for the performance of physical activities .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its understanding will grant advancement in the elaboration and execution of public policies. As a result, specific strategies, along with adequate and well-accepted mechanisms by the population, will allow the recognition of the characteristics and main interests of individuals 19 for the promotion of PA in leisure 18 .…”
Section: Introductionmentioning
confidence: 99%